2020
DOI: 10.1371/journal.pone.0227476
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care diagnostic (POCD) method for detecting Bursaphelenchus xylophilus in pinewood using recombinase polymerase amplification (RPA) with the portable optical isothermal device (POID)

Abstract: The pinewood nematode (PWN), Bursaphelenchus xylophilus, is a causative agent of pine wilt disease (PWD). To date, although several molecular diagnostic methods have been developed, rapid on-site diagnostic tools for detecting PWN in pinewood are limited. In this study, a point of care diagnostic (POCD) method for detecting PWN in pinewood using recombinase polymerase amplification (RPA) assay was developed. This method comprises quick gDNA extraction buffer (DAP buffer) for the direct extraction of gDNA of PW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…To this end, we diluted our in vitro-transcribed TMV RNA down to femtomolar concentrations and subjected the serial dilutions to our iSCAN-OP detection assay with the S3 set of RPA primers together with a ssDNA FAM fluorescent reporter to measure fluorescence in real-time. Our results indicate that our CRISPR-based detection assay can detect viral RNA down to the picomolar range, however, longer reaction time can improve the detection limit of the assay down to femtomolar, which is in line with previously reported data ( Figure 3B; Cha et al, 2020). However, we noticed that a longer incubation period was required for the effective detection of viral RNA molecules at low concentrations.…”
Section: Multiplexing and Sensitivity Of The Iscan-op Detection Assaysupporting
confidence: 92%
“…To this end, we diluted our in vitro-transcribed TMV RNA down to femtomolar concentrations and subjected the serial dilutions to our iSCAN-OP detection assay with the S3 set of RPA primers together with a ssDNA FAM fluorescent reporter to measure fluorescence in real-time. Our results indicate that our CRISPR-based detection assay can detect viral RNA down to the picomolar range, however, longer reaction time can improve the detection limit of the assay down to femtomolar, which is in line with previously reported data ( Figure 3B; Cha et al, 2020). However, we noticed that a longer incubation period was required for the effective detection of viral RNA molecules at low concentrations.…”
Section: Multiplexing and Sensitivity Of The Iscan-op Detection Assaysupporting
confidence: 92%
“…Another recently developed isothermal amplification technique is the so-called recombinase polymerase amplification (RPA) (Piepenburg et al, 2006). RPA is becoming a common choice when POC analysis is required for application in agriculture (Ahmed et al, 2018;Burkhardt et al, 2019;Strayer-Scherer et al, 2019) and forestry (Cha et al, 2020), as it presents several advantages when compared to PCR and even to LAMP. In fact, RPA does not require an initial heating step for DNA denaturation, as it exploits enzymatic activity to separate the double strand.…”
Section: Isothermal Nucleic Acid Amplificationmentioning
confidence: 99%
“…Moreover, the reaction temperature is quite low (37 to 42 • C), and the reaction time is usually very short (Kappagantu et al, 2017;Munawar et al, 2019). When RPA was compared to RT-LAMP as a detection method using a small (150 mm × 200 mm × 35 mm) and light (400 g) batterymounted portable optical isothermal device (Cha et al, 2020), the detection limit of RPA was shown to be 10 times lower than RT-LAMP. All these characteristics make RPA a very easy-to-use approach, especially in developing countries when fast analysis in low resource environments is needed (Wambua et al, 2017;Ghosh et al, 2018;Silva et al, 2018).…”
Section: Isothermal Nucleic Acid Amplificationmentioning
confidence: 99%
“…Real-time RPA detection assay of plant parasitic nematodes was first designed and published by Subbotin et al [ 23 ] for Meloidogyne enterolobii. RPA assays were also developed for Meloidogyne javanica , M. arenaria and M. incognita [ 24 , 25 ] and Bursaphelenchus xylophilus [ 26 , 27 ]. Recently, Song et al [ 28 ] described diagnostics of Meloidogyne hapla using RPA combined with a lateral flow dipstick assay, where species-specific primers and a probe were designed based on the effector gene 16D10 sequence.…”
Section: Introductionmentioning
confidence: 99%